Marriage Market Mismatches in Japan: An Alternative View of the Relationship between Women's Education and Marriage - Raymo, James M.; Iwasawa, Miho (American Sociological Review, 2005)
In Japan, unlike in most other industrialized societies, the decline in marriage rates has been most pronounced among highly educated women. Theoretical interpretations of this distinctive pattern of change have typically emphasized increasing economic independence for women and reductions in the gains to marriage. In this paper, the authors develop and evaluate an alternative explanation that emphasizes women's continued dependence on men's economic resources and decline in the relative supply of highly educated men. Using data from four rounds of the Japanese National Fertility Survey, the authors decompose the observed decline in marriage rates into changes in the propensity to marry and changes in the educational composition of the marriage market. Results indicate that change in the availability of potential spouses accounts for one-fourth of the decline in marriage among university-educated women and explains a substantial proportion of the growing educational differences in marriage. The conclusion is that the relatively large decline in marriage among highly educated Japanese women likely reflects both increasing economic independence and continued economic dependence on men.